2011
DOI: 10.1039/c1jm12230d
|View full text |Cite
|
Sign up to set email alerts
|

Non-IPR endohedral fullerene Yb@C76: density functional theory characterization

Abstract: With a combined methodology of quantum chemistry and statistical mechanics, two Yb@C 76 isomers are disclosed to possess novel fullerene structures which contain one pair of adjacent pentagons and are related by a single Stone-Wales transformation.Fullerenes synthesized to date satisfy the isolated-pentagon rule (IPR), which states that each pentagon on a fullerene cage should be surrounded by hexagons in a stable fullerene isomer. 1,2 However, non-IPR fullerene cages with abutting pentagons are also attractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 40 publications
1
40
0
3
Order By: Relevance
“…(S3), the nearest space between C 60 and rutile (1 1 0) surface is measured as 2.52 Å. And the CÀC bond length of C 60 is 1.39 and 1.44 Å, respectively, corresponding with our recently reports [35][36][37]. The binding energy (4.17 eV) of C 60 and rutile (1 1 0) is larger than that of graphene and rutile (1 1 0) in the neutral state.…”
Section: Modeling Of C 60 /Rutile (1 1 0) Compositesmentioning
confidence: 99%
“…(S3), the nearest space between C 60 and rutile (1 1 0) surface is measured as 2.52 Å. And the CÀC bond length of C 60 is 1.39 and 1.44 Å, respectively, corresponding with our recently reports [35][36][37]. The binding energy (4.17 eV) of C 60 and rutile (1 1 0) is larger than that of graphene and rutile (1 1 0) in the neutral state.…”
Section: Modeling Of C 60 /Rutile (1 1 0) Compositesmentioning
confidence: 99%
“…However, few studies are devoted to the different properties between metal‐containing and organically modified fullerene derivatives until now. We have reported that some endohedral metallofullerenes possess the stronger UV–vis–NIR broad band than pristine fullerene cages in recent studies,[18, 19] which encourages a further effort on investigating different physical properties between metal‐containing and organically modified fullerenes. Based on experimental reports, the electronic structures and optical spectra properties of five representative fullerene derivatives (three metal‐containing fullerenes and two organically modified ones), that is, Sc 3 N@C 80 , Pd{C 60 [P(CH 3 ) 3 ] 2 }, Pt(C 60 ) 2 , C 60 [C(COOMe) 2 ], and C 2 (C 60 ) 2 have been examined in this work.…”
Section: Introductionmentioning
confidence: 93%
“…107 Two Yb@C 76 isomers obtained experimentally have been found to possess the novel non-IPR cages with one pair of adjacent pentagons. 108 The electronic structure and thermodynamic stability of dimetallofullerene Lu 2 @C 76 have been investigated by means of a combined quantum chemical and statistical thermodynamic method. It was found that Lu 2 @C 76 (T d ), contains a single metal-metal bond between two Lu atoms.…”
Section: Endohedral Fullerenesmentioning
confidence: 99%